(untitled) (International Journal of Studies in Nursing, 2023)
Background: Breaking bad news in a clinical setting can lead to a negative experience for the healthcare provider when delivered inappropriately. This Doctor of Nursing Practice (DNP) Practice Innovation Project seeks to discover if healthcare providers who receive formal education in breaking bad news to patients have increased self-efficacy in breaking bad news compared with healthcare providers not formally educated in a DNP Program. This comparison was analyzed using a pre-test/post-test format. Purpose: The purpose of this DNP Practice Innovation Project is to improve the healthcare provider’s self-efficacy in breaking bad news to a patient through an educational module outlining the SPIKES protocol, ultimately improving the experience for the healthcare provider. Methodology: Participants included students enrolled in the DNP program in the Saint Mary’s College Department of Nursing Science. The SE-12 self-efficacy tool measured the participants’ self-efficacy utilizing a pre-test/post-test method that measured self-efficacy before and after the presentation of the educational module. The data from the pretest and posttest were analyzed using a two-tailed paired samples t-test. Results: The result was significant, suggesting the difference in the mean overall score of the SE-12 pretest and the mean overall score of the SE-12 posttest was significantly different from zero. The mean overall score of the SE-12 pretest was significantly lower than the mean overall score of the SE-12 posttest. Conclusion: This study established how education about breaking bad news can lead to an improved experience for the healthcare provider, ultimately improving health outcomes.